Effect of exercise training on cardiac autonomic function in type 2 diabetes mellitus: a systematic review and meta-analysis - Sohini Raje; G Arun Maiya; Padmakumar R; Mukund A. Prabhu; Krishnananda Nayak; Shivashankara KN; BA Shastry; Megha Nataraj (Systematic Reviews)
Abstract Background Cardiac autonomic neuropathy (CAN) is an underdiagnosed complication of type 2 diabetes mellitus (T2DM) and is associated with cardiovascular morbidity and mortality. Cardiac autonomic reflex tests (CARTs) are the gold standard; they are non-invasive and clinically feasible for screening CAN. The objective of the present meta-analysis was to examine exercise’s effect on cardiac autonomic function using CARTs in T2DM. Methods The Preferred Reporting Items for Systematic Review and Meta-Analysis Checklist (PRISMA) was used. Electronic databases were systematically used to retrieve relevant studies after title and abstract screening. Studies utilizing exercise training with cardiac autonomic function (CARTs) outcomes in individuals with type 2 diabetes mellitus were included. The meta-analysis was conducted using RevMan 5.4.1, using the random effects model, and appropriate tests for heterogeneity. The Cohrane ROB-2 tool was used for randomized controlled trials (RCTs) and the ROBINS-I tool for non-RCT for risk of bias assessment were used. Results Three studies were included (two for meta-analysis), considering the outcome of the E:I ratio, 30:15 ratio, and Valsalva ratio. The studies did not show any influence on the E:I and 30:15 ratio in the pooled analysis with a low risk of ineffectiveness for the exercise intervention. Exercise training significantly affected the Valsalva ratio. A different type of exercise intervention was utilized in all three studies. There was a low to moderate certainty for the evidence. Conclusion The results indicate that further robust and high-quality randomized controlled trials utilizing cardiac autonomic reflex tests (which have clinical and physiological relevance) in type 2 diabetes mellitus are required for drawing conclusions. Systematic review registration PROSPERO CRD42023445561.